Pest consumption by common bats in diverse landscapes - Miren Aldasoro; Oihane Diaz de Cerio; Nerea Vallejo; Lander Olasagasti; Joxerra Aihartza (PLoS ONE, 2026)
Insectivorous bats are increasingly recognised for their role in suppressing agricultural pests. To better understand the value of their ecosystem services, it is pertinent to assess their predation quantitatively. In this context, studying frequent anthropophilic bats that form large colonies is particularly interesting, as the ecosystem services they provide are more substantial. Building on this motivation, we analysed the diet of six horseshoe bat colonies—three Rhinolophus hipposideros and three R. ferrumequinum —across different landscapes within their optimal distribution area, focusing on their consumption of those pests. We found that these bats consistently consumed a variety of pests, with consumption correlating with outbreaks of the pest species. Some of these species were previously unknown in the area or were not fought against by farmers. This underscores the value of bats as sensitive trackers of current and emerging insect communities and potential pests, as they can detect and consume species that may go unnoticed or unmonitored by conventional human surveys. Additionally, we estimated the overall pest consumption by these bat species in the study area and assessed consumption at the colony level. Our estimates indicate that pest consumption during the breeding season totalled nearly 3 tons of insects. These findings underscore the importance of maintaining favourable habitats for common bats as they can play a vital role in controlling and mitigating ecosystem imbalances caused by changes in farming practices, landscape disturbances, or climate change.